2008
DOI: 10.1055/s-2007-965126
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Ankle Taping after a Training Session

Abstract: This study aimed to test the effectiveness of ankle taping on the limitation of forced supination during a change of direction, as well as the losses of effectiveness after a 30-minute training session. Fifteen young men with no ankle injury volunteered for the study. The static and dynamic ranges of movement (ROM) were measured before and after a training session. The dynamic measurements were recorded using high-speed 3D photogrammetry. The differences between static and dynamic measures of ankle supination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
1
18
0
1
Order By: Relevance
“…Similarly, the effects of ankle tape-protective or otherwise-over time remain to be quantified. The effectiveness of ankle tape decreases considerably after 10-20 min of exercise (28,33). Meana et al (28) reported a loss in dynamic support of over 40% after a 30-min bout of exercise in athletes using ankle tape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the effects of ankle tape-protective or otherwise-over time remain to be quantified. The effectiveness of ankle tape decreases considerably after 10-20 min of exercise (28,33). Meana et al (28) reported a loss in dynamic support of over 40% after a 30-min bout of exercise in athletes using ankle tape.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of ankle tape decreases considerably after 10-20 min of exercise (28,33). Meana et al (28) reported a loss in dynamic support of over 40% after a 30-min bout of exercise in athletes using ankle tape. Our testing sessions were typically 20-30 min in duration; therefore, our results may not reflect the injury risk faced by sportspeople participating in events of longer duration.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in ankle ROM (or perceptions) pre-to post-exercise, supporting the hypothesis. Work from other teams has shown that the effectiveness of ankle taping or spatting wanes with increasing physical activity, even in as little as 15 min [32][33][34]. The present results suggest that high-top shoes may be a substitute for ankle taping or spatting as the shoe may hold its effects over time.…”
Section: Range-of-motionmentioning
confidence: 58%
“…The measurements obtained from the footprint were taken according to the protocol described in Meana et al [30] . The footprint ( • ▶ Fig.…”
Section: Instrumentationmentioning
confidence: 99%